2019
DOI: 10.3390/polym11061048
|View full text |Cite
|
Sign up to set email alerts
|

Bioapplications of Bacterial Cellulose Polymers Conjugated with Resveratrol for Epithelial Defect Regeneration

Abstract: Excellent wound dressing is essential for effective wound repair and regeneration. However, natural polymeric skin substitutes often lack mechanical strength and hydrophilicity. One way to overcome this limitation is to use biodegradable polymers with high mechanical strength and low skin-irritation induction in wet environments. Bacterial cellulose (BC) is an attractive polymer for medical applications; unlike synthetic polymers, it is biodegradable and renewable and has a strong affinity for materials contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…P(3HB/4HB) combined with bacterial cellulose exhibited vastly improved wound healing by day 14 and when combined with fibroblasts, the wound was nearly completely sealed by this time. These results demonstrate that bacterial cellulose is a viable natural scaffolding material for wound healing that can exhibit loading potential for advanced therapeutics [109,110].…”
Section: Bacterial Cellulose Scaffoldsmentioning
confidence: 79%
See 1 more Smart Citation
“…P(3HB/4HB) combined with bacterial cellulose exhibited vastly improved wound healing by day 14 and when combined with fibroblasts, the wound was nearly completely sealed by this time. These results demonstrate that bacterial cellulose is a viable natural scaffolding material for wound healing that can exhibit loading potential for advanced therapeutics [109,110].…”
Section: Bacterial Cellulose Scaffoldsmentioning
confidence: 79%
“…It has recently been combined with copolymer P(3HB/4HB), a polyhydroxyalkanoate (PHA) derived from microbes and having similar qualities to bacterial cellulose itself, to develop scaffolds for managing burns [109]. It was also recently conjugated with resveratrol, a noncytotoxic naturally derived chemical that was thought to reduce inflammation and stimulate angiogenesis [110]. Both studies demonstrated favorable results with the use of bacterial cellulose as a scaffolding material, but according to in vivo experimental results in mouse models, the resveratrol-loaded bacterial cellulose scaffold may have inhibited wound reepithelialization compared with the scaffold alone by day 14, with 10% of the wound remaining without resveratrol and 20% remaining with resveratrol.…”
Section: Bacterial Cellulose Scaffoldsmentioning
confidence: 99%
“…In this study, the skin tissue healed with minimal complications and was found to promote cell proliferation during wound healing [103]. Suspension of BC with TiO 2 solution to enhance its anti-microbial capability has also been used to accelerate wound healing rate in vivo [104] as has resveratrol which has been shown to promote anti-inflammatory responses and enhance revascularization when incorporated with BC proving to accelerate skin regeneration [105]. The integration of stem cells with combinations of BC and acrylic acid composite scaffolds have proven to provide a moderately successful solution for full thickness dermal tissue wound healing [106].…”
Section: Medical Application and Marketed Products From Bacterial Celmentioning
confidence: 84%
“…These special characteristics are the main reasons for the extensive use of BC in biomedical and clinical settings than those of PC. The positive outcomes of BC usage in wound healing have been confirmed through in vivo and in vitro testing [ 66 , 67 , 68 , 69 , 70 ], as described in Table 3 . For instance, Wen et al (2015) have shown the efficiency of BC when incorporated with silver sulfadiazine in wound healing, by using a Wistar rat model with a partial thickness of a burn wound [ 114 ].…”
Section: Bacterial Cellulose For Wound Healingmentioning
confidence: 95%